The Relationship Between Knowledge And Skills of Posyandu Cadres Through The Zero Triple Program For Stunting Prevention In Bubulak Village, Bogor City - Nasrul Hidayat; Nain Azizah; Ning Ayu Zukhruf Jannah; Putri Fitria Ramadhani; Salma Prameswari Nursaadah (CV. Inara, 2025)
Background: Stunting remains one of the major nutritional problems affecting children's growth and development in Indonesia, including in Bogor City. Posyandu cadres play a crucial role in providing education and implementing stunting prevention efforts. However, limited knowledge and practical skills among cadres in carrying out these activities in the field remain significant challenges that need to be addressed. Objective: This study aims to determine the relationship between the level of knowledge and skills of Posyandu cadres through the implementation of the Zero Triple Program and their efforts in stunting prevention in Bubulak Subdistrict, Bogor City. Method: This study employed a quantitative descriptive method with a pre-experimental one-group pretest–posttest design. The program was conducted over four sessions involving 21 Posyandu cadres. The stages included preparation, socialization and program introduction, delivery of balanced nutrition materials through the Isi Piringku educational game demonstration, training on tilapia fish and hydroponic cultivation, demonstration of tilapia dim sum processing, as well as mentoring and evaluation through pre-test and post-test assessments. The data obtained were then processed and analyzed using Microsoft Excel Results: The average pre-test score increased from 17.0 to 19.4 for the stunting material, 18.0 to 19.5 for the balanced nutrition material, and 1.19 to 2.10 for the hydroponic cultivation and tilapia processing training. These results indicate a significant improvement in the knowledge and skills of respondents after participating in the zero triple program. Conclusion: There is a significant relationship between the implementation of the zero triple program and the improvement of Posyandu cadres' capacity in delivering education and practical stunting prevention efforts in Bubulak Village, Bogor City. Suggestion: Future studies are recommended to involve a larger number of respondents and include an evaluation of cadres' behavioral changes following the training program to strengthen the sustainability and impact of community-based stunting prevention initiatives.